The Concept of Islamic Education Based on Religious Humanism Said Nursi's Perspective - Afif Alfiyanto; Syamsul Rijal; Silahuddin Silahuddin (Departement of Mathematics Education, 2023)
Said Nursi's first effort was to make people aware of the importance of education, where Islam is